THE EFFECT OF SOCIAL MEDIA USE ON INCREASING MSME SALES IN TIMOR-LESTE - Aderila Guteres (EKSPOLHUM, 2026)
The transformation of the contemporary marketing landscape requires Micro, Small, and Medium Enterprises (MSMEs) to adopt digital channels to maintain operational competitiveness and expand market share. In Timor-Leste, digital adoption dynamics face a structural gap between high strategic awareness and low functional integration of social media into sales governance. This study aims to empirically analyze and measure the effect of social media utilization on increasing MSME sales in Timor-Leste. Grounded in the Technology Acceptance Model (TAM) framework and digital marketing theory, this quantitative correlational study involved 120 MSME owners or managers across Dili, Baucau, and Maliana selected via purposive sampling. Primary data were gathered through structured questionnaires using a five-point Likert scale and analyzed using simple linear regression via SPSS version 26. Instrument testing confirmed that all items were valid and reliable (), satisfying normality and linearity assumptions. The regression results demonstrate that social media utilization has a positive and significant effect on MSME sales growth in Timor-Leste (, ). The coefficient of determination () of 0.431 indicates that 43.1% of the variance in sales volume increase is explained by the intensity and effectiveness of social media utilization, while the remaining 56.9% is influenced by other external variables. These findings underscore the urgency of strengthening digital literacy, improving connectivity infrastructure, and formulating community interactivity-based content strategies for business actors in post-conflict developing nations.